2022
DOI: 10.1039/d1cc06088k
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvents comprising creatine and citric acid and their hydrated mixtures

Abstract: We report the phase diagram for the binary creatine–citric acid mixture which features a stable and broad eutectic region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…[12d,47b,87] In addition, the investigation of deep eutectic solvent mixtures with B30 and other solvatochromic indicators has become a popular subject of investigation. [80,81,128,129] The application of the pKa rule to assess proton transfer or hydrogen bond formation is an essential prerequisite for the correct analysis of solvatochromism in these solvent systems. For example, dubious (too large) E T (30) values for solvent systems containing citric acid are reported without critical discussion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12d,47b,87] In addition, the investigation of deep eutectic solvent mixtures with B30 and other solvatochromic indicators has become a popular subject of investigation. [80,81,128,129] The application of the pKa rule to assess proton transfer or hydrogen bond formation is an essential prerequisite for the correct analysis of solvatochromism in these solvent systems. For example, dubious (too large) E T (30) values for solvent systems containing citric acid are reported without critical discussion.…”
Section: Discussionmentioning
confidence: 99%
“…[128] However, other authors have carefully checked and found that this solvent system cannot be measured with B30. [129] The central aspect of the density of the solvent mixture in relation to the involved, proportionate molar masses of constituents is a decisive factor. Precise density measurements as a function of composition in mixtures of organic solvents and with ILs are an essential basis for arriving at physically correct statements in connection with solvatochromic measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 In line with green chemistry principles and sustainability requirements, the search for ‘truly’ green solvents for the dissolution of biopolymers such as PHAs is essential. 19 To provide such green dissolution media, Abbott et al 20 discovered deep eutectic solvents (DESs) in 2003 and their applications have grown by leaps and bounds in about two decades. 21 A DES is a eutectic mixture of a hydrogen-bond donor (HBD) and a quaternary ammonium or phosphonium salt resulting in a liquid with a melting point below that of its individual components.…”
Section: Introductionmentioning
confidence: 99%